2020
DOI: 10.5852/ejt.2020.616
|View full text |Cite
|
Sign up to set email alerts
|

Cestode parasites (Neodermata, Platyhelminthes) from Malaysian birds, with description of five new species

Abstract: We studied the cestode fauna (Platyhelminthes) of forest birds in Malaysia (Selangor) collected during a field trip in 2010. Ninety birds of 37 species were examined and global prevalence of cestodes was 15.3%. Five new taxa are described: Emberizotaenia aeschlii sp. nov. (Dilepididae) from Tricholestes criniger (Blyth, 1845) (Pycnonotidae); Anonchotaenia kornyushini sp. nov. (Paruterinidae) from Trichastoma malaccense (Hartlaub, 1844) (Pellorneidae); Biuterina jensenae sp. nov. (Paruterinidae) from Chloropsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 716 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In comparison, Abbas (37) found that S. senegalensis in Babylon province was infected with tapeworms Raillietina spp. Raillietina hymenolepidoides was first isolated from F. francolinus in Iraq, and Mariaux and Georgiev (38) were the first to record this type of worms, R. hymenolepidoides sp. nov., in the Malaysian on dove Chalcophaps indica.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, Abbas (37) found that S. senegalensis in Babylon province was infected with tapeworms Raillietina spp. Raillietina hymenolepidoides was first isolated from F. francolinus in Iraq, and Mariaux and Georgiev (38) were the first to record this type of worms, R. hymenolepidoides sp. nov., in the Malaysian on dove Chalcophaps indica.…”
Section: Discussionmentioning
confidence: 99%
“…Dissections, fixation and staining were performed according to standard procedures (see e.g. Mariaux & Georgiev, 2020), and stained specimens were mounted in Canada balsam. Some scoleces were squashed in Berlese's medium to facilitate examination of rostellar hooks.…”
Section: Methodsmentioning
confidence: 99%